Problems And Innovations Of Educational Institutions - Lia Eviyanti; Ahmad Nu’man Farisi; Yuyun Rohmatul Uyuni; Machdum Bachtiar (Formosa Journal of Science and Technology, 2024)
Education follows the changes of an era, if not adjusted, education will fail to educate the nation's generation. Therefore, in education, innovation is needed which can provide updates that can add knowledge and insight to students and also update about other sciences so as not to be left behind. Also with innovation in the field or educational institutions, it is hoped that it will be able to achieve a better and more directed quality of education. The purpose of this research is to find out how the problems and innovations of the Educational Institutions. The method used in writing this article is the library research method or literature review study. Based on the results of the research, it is concluded that there are several problems of Islamic religious education institutions that all need to be overcome if Islamic religious education is to be improved in the future. Therefore, learning reform needs to be implemented.